Profiles of Risk for Suicidal Behavior in Past and Current United States Military Personnel: Latent Profile Analysis of Current Risk Factors. Issue 1 (2nd January 2020) - Allan, Nicholas P.; Holm-Denoma, Jill; Conner, Kenneth R.; Zuromski, Kelly L.; Saulnier, Kevin G.; Stecker, Tracy
Abstract : Person-centered approaches are underutilized to identify people with shared risk profiles. In this study, an at-risk sample of 773 past/current military personnel ( M age = 31.3 years, SD  = 6.8) with current ideation (90.6%) and/or a prior suicide attempt (43.9%) were assessed using latent profile analysis. Variables included prior suicide attempts, suicidal ideation, alcohol/drug use, insomnia, depression, belongingness, burdensomeness, and post-traumatic stress disorder symptoms. Three classes emerged: Low Symptoms ( N  = 502), Elevated Suicidality ( N  = 176), and Elevated Substance Use ( N  = 95). At 1-month follow-up, the Elevated Suicidality and Elevated Substance Use classes had the highest odds of suicidal behavior. The finding concerning the Elevated Substance Use class suggests it may represent a distinct short-term risk group in military personnel.